Answer:
x=6,
y=-9,
z=7
Explanation:
Rewrite the second equation in the first place
![\left\{\begin{array}{l}x+3y-z=-28\\2x+y-2z=-11\\3x+4y-z=-25\end{array}\right..](https://img.qammunity.org/2020/formulas/mathematics/middle-school/iwsjo0fpmgnlqut09mse2fwwwyht3il0vx.png)
Multiply the first equation by 2 and subtract the second and then multiply the first equation by 3 and subtract the third:
![\left\{\begin{array}{l}x+3y-z=-28\\2x+6y-2z-(2x+y-2z)=-2\cdot 28-(-11)\\3x+9y-3z-(3x+4y-z)=-3\cdot 28-(-25)\end{array}\right.\Rightarrow \left\{\begin{array}{r}x+3y-z=-28\\5y=-45\\5y-2z=-59\end{array}.](https://img.qammunity.org/2020/formulas/mathematics/middle-school/s4w4ivkk80x06enoxm98pfp3stgefha9hq.png)
Write the variable y into the third column:
![\left\{\begin{array}{r}x-z+3y=-28\\-2z+5y=-59\\5y=-45\end{array}.](https://img.qammunity.org/2020/formulas/mathematics/middle-school/dcjfwhnapap2y2azxk543swbb32i507yq1.png)
From the last equation
![y=-(45)/(5)=-9.](https://img.qammunity.org/2020/formulas/mathematics/middle-school/23jo1rrapamogjrmwnu5yq3nm3f8bx4rjy.png)
Substitute it into the previous equation:
![-2z+5\cdot (-9)=-59,\\ \\-2z=-59+45,\\ \\-2z=-14,\\ \\z=7.](https://img.qammunity.org/2020/formulas/mathematics/middle-school/p3yxtns2sj91vzp740pp6dqw23hg7qbowt.png)
Substitute both y and z into the first equation:
![x+3\cdot (-9)-7=-28,\\ \\x=-28+7+27,\\ \\x=6.](https://img.qammunity.org/2020/formulas/mathematics/middle-school/uamzy9hbjwyx2a6vi14lbljsg64qncrfmh.png)